EFEKTIVITAS MODEL PEMBELAJARAN SIMULASI BERBANTUAN PERMAINAN GEO EXPLORE PADA MATA PELAJARAN GEOGRAFI SISWA KELAS XI IIS SMA NEGERI 2 SEMARANG (Edu Geography, 2016)
The purposes of this research to know effectiveness simulation learning model helped â€œGeo Exploreâ€ game from accomplishment of student learning activity, student learning result, positive student respons and teaching skill, also to know the correlation of student learning activity in simulation learning model with Geography learning result. The research methods is pre-experimental with â€œone group pre-test post-testâ€design. The population of the research are students of Class XI IIS SMA Negeri 2 Semarang. The sample are students of Class XI IIS 1 total 29 students. Data analisys using descriptive, t-test, and product moment correlation test. The reserach result show student learning activity is very high, average score 52,62 or 87,70%. Student learning result is proven by two side t-test, thitung > ttabel or 7,56 > 2,05, so Ho is rejected, post-test result is better than pre-test result. The accomplishment of student learning result is proven by one side t-test, result thitung > ttabel or 5,03 > 1,70, so Ho is rejected, student learning result is done. Classical accomplishment 86,21%. Score of positive respons is good 64,28 or 73,04%. The category of teaching skill is good, score 18 or 64,29%. Product moment correlation test is showed rhitung <Â  rtabel or 0,155 < 0,367, Ho is rejected, so there is not correlation between students learning activity with Geography learning result.